Cheap Print and Street Literature of the Long Eighteenth Century - Atkinson, David; Roud, Steve (Open Book Publishers, 2023)
This deeply researched collection offers a comprehensive introduction to the eighteenth-century trade in street literature - ballads, chapbooks, and popular prints - in England and Scotland. Offering detailed studies of a selection of the printers, types of publication, and places of publication that constituted the cheap and popular print trade during the period, these essays delve into ballads, slip songs, story books, pictures, and more to push back against neat divisions between low and high culture, or popular and high literature. The breadth and depth of the contributions give a much fuller and more nuanced picture of what was being widely published and read during this period than has previously been available. It will be of great value to scholars and students of eighteenth-century popular culture and literature, print history and the book trade, ballad and folk studies, children's literature, and social history.